PERAN LITERASI DIGITAL DALAM MEMPERSIAPKAN MAHASISWA PGSD UNJA UNTUK ERA DIGITAL - Dhea amanda alfa rezki; Zhafira sayyidatunnisa; Oliver Chelsea Sitanggang; Akhmad faisal hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the role of digital literacy in preparing PGSD students of the University of Jambi (UNJA) to face challenges in the digital era. The method used in this study is a qualitative descriptive method, with a literature study approach to collect data from various sources, such as books, journals, and relevant reports. The results of the study show that digital literacy has a crucial role in helping students access information quickly and widely, as well as supporting the development of critical, analytical, and creative thinking skills needed in the teaching profession. Therefore, it is important for PGSD UNJA students to develop digital literacy wisely, utilize technology effectively, and maintain a balance between digital and traditional literacy. This research emphasizes that with the right approach, digital literacy can have a maximum positive impact in preparing students to become competent and adaptive teachers in the ever-changing digital era.